Factors Influencing Behavioral Intentions In Maritime Cargo Transport Services At Bangkok Port : Service Users’ Perspectives - Jakparinyakul, Suwimol; Boonchunnone, Surasidh (Journal of KMITL Business school, 2024)
This research aims to (1) examine the factors influencing transaction satisfaction with maritime cargo transport services at the Port of Bangkok from the users’ perspective and (2) examine the factors influencing behavioral intentions, including empathy, reliability, assurance, tangible, responsiveness and satisfaction in providing maritime cargo transport services at the Port of Bangkok from the perspective of service users. The study is quantitative with 380 sample size service users selected through simple random sampling. The statistical methods used include descriptive statistics and multiple regression analysis. The research findings indicate that logistics service quality, including empathy, assurance, tangible service, and responsiveness, significantly influences transactional satisfaction. Additionally, tangible service, responsiveness, and transactional satisfaction significantly positively influence behavioral intentions. This study provides valuable insights for researchers, companies, and organizations involved in cargo transportation services to enhance logistics service quality and positively influence behavioral intentions. Keywords: Logistics service quality, Transaction satisfaction, Behavioral intention